(untitled) (International relations and international law Journal, 2019)
Modern challenges take place in markets force the companies’ management to cope with risks and uncertainty. To forward competitive advantages, it is important to develop skills necessary to solve emerging problems. The authors attempted to reveal needed soft skills to manage organizations effectively. The purpose of scientific research is to study the degree of awareness concerning the soft skills concept among Kazakhstani employees. Due to the selected survey approach, the data are reliable but exploratory one. Thus, representative data is needed to confirm the findings. Online survey with the nonrepresentative sample of employed people working in business companies was conducted. There were two stages of the research. The first stage was exploratory secondary research. Secondary data helped to propose the hypothesis that poor soft skills lead to poor performance of any activity where people interact. Findings taken from online survey showed that 54.8 % of respondents consider that soft skills are important. 64.5% claimed that low level of awareness on soft skills leads to poor performance. There can be no doubt that awareness of employees on soft skills will increase their personal performance. Within the paper, the discussion focuses on the importance for Kazakhstani entrepreneurs, businesspersons and employees to develop soft skills to expand boundaries of career opportunities. Key words: soft and hard skills, leadership, innovators, change, project, team.